The Roles of Body Composition and Specific Strength in the Relationship Between Race and Physical Performance in Older Adults. (11th December 2019) - Chiles Shaffer, Nancy; Simonsick, Eleanor M; Thorpe, Roland J; Studenski, Stephanie A
Abstract: Background: Socioeconomics may explain black–white differences in physical performance; few studies examine racial differences among socioeconomically similar groups. Performance is also affected by body composition and specific strength, which differ by race. We assessed whether racial differences in physical performance exist among older adults with high education and similar income and whether body composition and specific strength attenuate observed differences. Methods: Cross-sectional analysis of 536 men (18% black) and 576 women (28% black) aged more than 60 years from the Baltimore Longitudinal Study of Aging. Body composition was evaluated using dual-energy x-ray absorptiometry. Specific strength was assessed by quadricep peak torque divided by height-normalized thigh cross-sectional area and grip strength divided by body mass index-normalized appendicular lean mass. Physical performance was assessed using usual gait speed and fast 400 m walk time. Sex-stratified linear regression models, adjusted for age, height, education, and recent income, determined whether body composition or specific strength attenuated associations between race and physical performance. Results: Blacks were younger, with higher weight and appendicular lean mass. Black women had higher percent fat and specific strength. In both sexes, blacks had poorer physical performance after adjustment for socioeconomic factors. In women, neither body composition nor specific strength altered the association with gait speed. In men, neither body composition nor specific strength attenuated racial differences in either performance measure. Conclusions: Poorer physical performance among black compared to white older adults persists among persons with high education and similar income and cannot generally be attributed to differences in body composition or specific strength.